Análise do alinhamento das 283 propostas nos três eixos aprovadas na 16ª conferência nacional de saúde (8ª + 8) – 2019 – com as políticas nacionais de saúde, como instrumento de gestão em saúde - Amaral, Nadir Francisco do (2020)
This work aims to present the analysis of the alignment of the 283 proposals approved by the 16th National Health Conference (8th + 8) based on the three thematic axes of the Conference: Health as a right; Consolidation of the Principles of the Unified Health System (SUS); Adequate and sufficient funding for SUS, with 49 National Health Policies (PNSs) stratified by groups. Through an exploratory and documentary study, with descriptive statistical processing. As a result, there were 159 (56.18%) aligned proposals, while 124 (43.82%) of non-aligned proposals showed political, economic or related to the need for human resources for the health sector. Among the main proposals were identified: National Policy for Strategic and Participative Management (ParticipaSUS); National Primary Care Policy; National Policy on Mental Health and National Policy on Information and Informatics in Education. It is concluded that the process and dynamics of the studied Conference constitute an important space for discussion and channeling demands and identification the needs of the actors and social segments involved.